Synthesis of Ba(Mg1/3Ta2/3)O-3 microwave dielectrics by solid state processing - Fang, YH; Hu, A; Gu, Y; Oh, YJ (ELSEVIER SCI LTD, 2003)
Synthesis and formation of Ba(Mg1/3Ta2/3)O-3 (BMT) from BaCO3, MgO and Ta2O5 was examined by thermal and X-ray diffraction analyses using quenching technique. Several reactions take place during heating process. BaCO3 can react with Ta2O5 to form BaTa2O6 (BT2) and B4T2. BT2 as an intermediate product was found at the first stage of the reaction, and then BaTa2O6 or B4T2 react with MgO to form BMT. The reaction of BMT formation was not complete until it was sintered at 1350 degreesC for 60 min. An intermediate reproduce cycle keeps company with the BMT formation in calcinations and sintering processing. The kinetics of solid-state reaction between powdered reactants for the reaction of BaTa2O6 formation was diffusion mechanism controlled, which can be described by Jander's model for three-dimensional diffusion. The activation energy was determined to be 235.6 kJ/mol. The BMT powders were sintered to similar to96% of relative density after 3 h at 1650 degreesC. The final sintered ceramics exhibited a dielectric constant of 24.5, a Q.f of 120,000 GHz, and a temperature coefficient of resonant frequency of 6 ppm/degreesC. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: CERAMICS